Ultrasonographic-guided robotic-assisted percutaneous nephrolithotomy - Stefano Bazzani; Stefano Puliatti; Stefania Ferretti; Giampaolo Bianchi; Cristian Secchi; Federica Ferraguti (Communications Engineering)
Abstract Percutaneous nephrolithotomy (PCNL) is considered the gold standard for treating kidney stones larger than 20 mm. However, the procedure requires high expertise and technical skills, especially for precise and accurate percutaneous access. This paper presents a robotic system designed to enable accurate kidney access by combining 3D anatomical modeling with real-time ultrasound guidance, thereby allowing novice surgeons to gain confidence in performing the initial puncture. A comprehensive validation campaign was conducted in a controlled clinical simulation environment, with experiments performed by both experienced urologists and urology residents. The proposed system improves surgical performance, reduces human error, and makes the procedure more accessible to less experienced clinicians.